Peran Konseling Mediasi dalam Mengatasi Perceraian - Takdir; Fajriani, Nurul (Indonesian Journal of Islamic Counseling, 2023)
The effort made by the Religious Court to cancel a divorce is through mediation. Mediation guidance is an effort to reconcile both parties in a dispute or disagreement, including people who want to divorce. Mediation guidance must be carried out optimally in order to handle divorce problems. The aim of this research is to find out how the mediation guidance process is carried out by the Parepare Religious Court. The research method uses a qualitative descriptive approach. The results of the research are that mediation guidance, if seen from the number of people who divorce, is not yet effective. However, if you look at the mediation guidance process carried out by the Parepare Religious Court, it has been very optimal and how mediation guidance should work in Islamic counseling guidance. Every mediator (Counselor) who carries out mediation guidance has made every effort so that people who previously wanted to divorce can be reconciled again. The Parepare Religious Court's efforts to optimize the mediation guidance process are also assisted by mediator judges (Counselors) who have special abilities and skills as mediators (Counselors).